Langurs in the Aegean Bronze Age? A Review of a Recent Debate on Archaeoprimatology and Animal Identification in Ancient Iconography - Binnberg, Julia; Urbani, Bernardo; Youlatos, Dionisios (Journal of Greek Archaeology, 2021)
Recently, an article was published in the journal Primates, in which an interdisciplinary team consisting of primatologists, a taxonomic illustrator, and an art historian/archaeologist suggested a new identification of the monkeys depicted in a wall painting from Room 6 of Building Complex Beta in the Bronze Age town of Akrotiri on the Cycladic island of Thera. Briefly summarised, Pareja et al. argued that the monkeys represented are to be identified as grey or Hanuman langurs (Semnopithecus spp.), a monkey genus native to the Indian subcontinent. With this, they diverged from the traditional identification as green monkeys/vervets/grivets of the genus Chlorocebus from Africa. It was claimed that the new identification as langurs provides (further) evidence for links between the Aegean and the Indus River Valley during the Bronze Age, with Mesopotamia as a likely intermediary region. According to the authors, the Cycladic artists could have seen langurs on their travels, and monkey iconography could have reached the Aegean via objects originating from these regions.